2011
DOI: 10.1128/jcm.00581-10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Group B Streptococcus Prosthetic Joint Infections and Molecular Characterization of Isolates

Abstract: Twelve group B Streptococcus (GBS) prosthetic joint infection (PJI) cases are reported. The mean patient age was 55 years. Eleven infections were caused by GBS alone. The associated isolates belonged to phylogenetic lineages different from those that cause neonatal meningitis. The clinical outcome was favorable for the eight patients for whom follow-up data were available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Of the CoNS, S. lugdunensis was the second most frequently isolated species after S. epidermidis, confirming its strong virulence, as reported previously (25). Concerning streptococcal infections, our study confirms the importance of Streptococcus agalactiae and shows the existence of true PJIs caused by the Streptococcus mitis and Streptococcus milleri groups (26). P. acnes infections represented 7% of monomicrobial anaerobic PJIs, which highlights its role in the pathogenicity of implant-associated infections (27).…”
Section: Discussionsupporting
confidence: 70%
“…Of the CoNS, S. lugdunensis was the second most frequently isolated species after S. epidermidis, confirming its strong virulence, as reported previously (25). Concerning streptococcal infections, our study confirms the importance of Streptococcus agalactiae and shows the existence of true PJIs caused by the Streptococcus mitis and Streptococcus milleri groups (26). P. acnes infections represented 7% of monomicrobial anaerobic PJIs, which highlights its role in the pathogenicity of implant-associated infections (27).…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies of streptococcal bone and joint infection have reviewed the clinical characteristics and the outcome of streptococcal arthritis or joint prosthesis infection by streptococcal groups classified by Lancefield and Sherman [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . Only a few studies of streptococcal bone and joint infection with well-identified species have been reported [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus is a diverse genus that has a prominent role in human disease but causes Ͻ10% of joint arthroplasty infections. A number of beta-hemolytic Streptococcus species cause PJI, including Lancefield groups A (145-147), B (148)(149)(150)(151)(152)(153), C (154)(155)(156), and G (145,157,158). Streptococcus gallolyticus subsp.…”
Section: Causative Microorganismsmentioning
confidence: 99%